To Question the consensus: Ricardo Piglia Rewrites the Argentinean Canon (Castilla. Estudios de Literatura, 2013)
The article focuses on the question of canon-building in Argentinean literature, according to Ricardo Piglia’s interpretation, First, the distinction is made between “canon”, a petrified hierarchy of texts, and “tradition”, an order which is dynamic and fertile for the actual literature. Later on, the term “canon” is applied in contexts larger than merely literary, that is, the linguistic and political ones. In this regard, two Piglia’s texts dedicated to the Gombrowicz’s diatribe “Against the poets” are examined.